The Alliance of Bioversity International and CIAT Annual Report 2022: People at the heart of food systems - Bioversity International; International Center for Tropical Agriculture (2023)
Discover research, case studies, and highlights encapsulating the Alliance of Bioversity and CIAT's mission to transform people's lives during a climate crisis. Highlights span: Land, Crops, Food, and Markets.